Atlas for the diagnosis of tumors in the dog and cat - Kiehl, Anita R.; Calderwood Mays, Maron B. (Ames, Iowa : Wiley Blackwell, 2016)
Atlas for the Diagnosis of Tumors in the Dog and Cat is a diagnostic tool for determining if samples are abnormal and defining the cause of the abnormality, with 386 clinical images depicting normal and abnormal results, the book begins by describing specific types of neoplasia. -Offers a brief overview of the methods used to produce a diagnosis and prognosis from a biopsy tissue sample -Pairs photographs of biopsy samples with photomicrographs of cells obtained via fine needle aspirate -Includes a useful chapter covering sample handling, staining, and shipping.
Principles of naming, grading, staging and determining a reasonable prognosis -- Selected lesions of the head and neck -- Selected lesions of the limbs, paws, and digits -- Selected genital and perineal masses -- Selected lesions of the skin and subcutis of the trunk -- Selected lesions of the thoracic viscera -- Selected lesions of the abdominal viscera -- Sample handling.
Includes bibliographical references and index.
Online resource, title from PDF title page (EBSCO), viewed September 15, 2016.
Keywords: Tumors -- Animal models -- Atlases; Tumors in animals -- Diagnosis; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry; Neoplasms -- veterinary; Neoplasms -- diagnosis; Neoplasms -- pathology; Prognosis; Dog Diseases; Cat Diseases; Electronic books; Electronic books; Atlases